Effect of Immunoglobulin Therapy on the Rate of Infections in Multiple Myeloma Patients Undergoing Autologous Stem Cell Transplantation and or Treated with Immunomodulatory Agents - Gerald Bates; Burns Denise; Amanda Cox; Matthias Maiwald; Alhossain A. Khalafallah; Terry Hannan; David Seaton; Bernadene Fernandopulle; Terry Brain (Mediterranean Journal of Hematology and Infectious Diseases)
There are few data available regarding the prevalence of infection in multiple myeloma (MM) patients in conjunction with newer generations of immunomodulatory drugs (thalidomide, bortezomib, lenalidomide) or post autologous stem cell transplantation. We retrospectively analyzed 47 patients with MM from March 2006 to June 2009 at our institution. All patients received thalidomide and steroid therapy for at least 6 months. Nine patients received bortezomib and 11 lenalidomide subsequently to thalidomide, because of disease progression and 22 patients underwent autologous stem cell transplantation. The median age was 64 years (range 37-86), with a female–to-male ratio of 18:29. The median residual-serum IgG-level at time of infection was 3.2 g/L, IgA 0.3 g/L and IgM 0.2 g/L. Most patients suffered from recurrent moderate to severe infections. All patients except 3 received intravenous immunoglobulin (IVIG) therapy with a significant decline of the rate of infection thereafter. Our analysis shows that IVIG appears to be an effective strategy to prevent infection in MM patients. Further studies to confirm these findings are warranted.